Volunteerism and volunteer management in sport. Issue 4 (August 2017) - Wicker, Pamela
Highlights: Reflection on existing research from individual, institutional, multi-level, and policy perspectives. Volunteerism has been widely studied from an individual perspective. From an institutional perspective, other dimensions of volunteer management than recruitment of volunteers and performance management should be examined. Future research should consider the multi-level and policy perspectives. Future studies should focus more on different groups of volunteers (coaches, referees). Abstract: This article reflects on existing research examining volunteerism and volunteer management in sport from individual, institutional, multi-level, and policy perspectives. The overview reveals that a substantial body of knowledge has been generated, particularly on the individual perspective and, to a lesser extent, on the institutional perspective. Existing studies from the individual perspective have mainly examined antecedents and experiences of volunteers in sport organizations and at sport events, focusing on topics such as motivation, commitment, and satisfaction, while consequences of volunteerism have attracted less research. On the institutional perspective, research efforts have focused on topics such as recruitment and retention of volunteers and performance management. Studies taking a multi-level perspective give indications about how the institutional or community context affects volunteerism and volunteer management. From a policy perspective, research has mainly looked at challenges for volunteerism resulting from policy implementation and the monetary value of voluntary work. The overview also reveals that many studies have examined the mass of volunteers in general or volunteers in leading positions, while other groups of volunteers, such as voluntary coaches and referees, have attracted less research. After reflecting on topics examined and key findings, the article provides suggestions for future research within each perspective, ensuring that all perspectives and groups of volunteers are attended to.